COVID-19 symptoms predictive of healthcare workers' SARS-CoV-2 PCR results - Lan, Fan Yun; Filler, Robert; Mathew, Soni; Buley, Jane; Iliaki, Eirini; Bruno-Murtha, Lou Ann; Osgood, Rebecca; Osgood, Rebecca; Christophi, Costas A.; Fernandez-Montero, Alejandro; Kales, Stefanos N. (My University, 2020)
Background Coronavirus 2019 disease (COVID-19) is caused by the virus SARS-CoV-2, transmissible both person-to-person and from contaminated surfaces. Early COVID-19 detection among healthcare workers (HCWs) is crucial for protecting patients and the healthcare workforce. Because of limited testing capacity, symptom-based screening may prioritize testing and increase diagnostic accuracy. Methods and findings We performed a retrospective study of HCWs undergoing both COVID-19 telephonic symptom screening and nasopharyngeal SARS-CoV-2 assays during the period, March 9.April 15, 2020. HCWs with negative assays but progressive symptoms were re-tested for SARSCoV- 2. Among 592 HCWs tested, 83 (14%) had an initial positive SARS-CoV-2 assay. Fiftynine of 61 HCWs (97%) who were asymptomatic or reported only sore throat/nasal congestion had negative SARS-CoV-2 assays (P = 0.006). HCWs reporting three or more symptoms had an increased multivariate-adjusted odds of having positive assays, 1.95 (95% CI: 1.10.3.64), which increased to 2.61 (95% CI: 1.50.4.45) for six or more symptoms. The multivariate-adjusted odds of a positive assay were also increased for HCWs reporting fever and a measured temperature . 37.5°C (3.49 (95% CI: 1.95.6.21)), and those with myalgias (1.83 (95% CI: 1.04.3.23)). Anosmia/ageusia (i.e. loss of smell/loss of taste) was reported less frequently (16%) than other symptoms by HCWs with positive assays, but was associated with more than a seven-fold multivariate-adjusted odds of a positive test: OR = 7.21 (95% CI: 2.95.17.67). Of 509 HCWs with initial negative SARS-CoV-2 assays, nine had symptom progression and positive re-tests, yielding an estimated negative predictive value of 98.2% (95% CI: 96.8-99.0%) for the exclusion of clinically relevant COVID-19. Conclusions Symptom and temperature reports are useful screening tools for predicting SARS-CoV-2 assay results in HCWs. Anosmia/ageusia, fever, and myalgia were the strongest independent predictors of positive assays. The absence of symptoms or symptoms limited to nasal congestion/sore throat were associated with negative assays.
Keywords: Adult; Ageusia; Asymptomatic Infections; Betacoronavirus; Body Temperature; Coronavirus Infections; Female; Fever; Health Personnel; Humans; Logistic Models; Male; Middle Aged; Multivariate Analysis; Myalgia; Nasopharynx; Olfaction Disorders; Pandemics; Pharyngitis; Pneumonia, Viral; Polymerase Chain Reaction; Principal Component Analysis; Retrospective Studies